PAPUAN VOICES IN PROSE: CONFLICT, RACISM, AND THE STRUGGLE FOR RECOGNITION - Irma Nuraeni Salsabila (Journal of Literary Prose and Society, 2025)
This article examines how contemporary Papuan prose articulates experiences of conflict, racism, and the struggle for recognition within the Indonesian context. Using a qualitative literary and cultural studies approach, the research analyzes a purposively selected corpus of twelve Papuan short stories and novels published between 2005–2023. Close reading and thematic–discourse analysis are employed to identify representations of physical and structural violence, forms of racialization, and narrative expressions of claims to recognition. The findings show that conflict is predominantly represented as a continuum of structural and economic violence that permeates everyday life, rather than as isolated military events. Racism appears in overt insults, stereotyping, institutional discrimination, symbolic erasure, and, in some cases, internalized feelings of inferiority. Across the texts, Papuan characters articulate multi-layered demands for recognition as human beings, citizens, and indigenous peoples, frequently using first-person narration, shifting focalization, symbolism, and code- switching to re-center Papuan subjectivity. The study extends previous scholarship on Papuan literature by foregrounding racism and recognition as central analytical categories and by highlighting the aesthetic and political sophistication of Papuan writers as knowledge producers. Practically, the research suggests that Papuan prose should be more systematically integrated into educational curricula and cultural policy to foster more just and inclusive understandings of Papua. The study’s limitations—particularly its small corpus and focus on Indonesian-language, published works—point to the need for broader, multilingual, and interdisciplinary investigations of Papuan cultural production.